Analisis Harga dan Kualitas Produk Terhadap Keputusan Pembelian Produk Avoskin - Meliana Rafa, Ovita; Siska, Elmira; Indra, Natal (Institut Nalanda, 2023)
This study aims to analyze the influence of price and product quality on consumer purchasing decisions for Avoskin products. The research method employed was a quantitative approach with primary data collected through questionnaires. The research sample consisted of 100 consumers of Avoskin products selected using the accidental sampling method. Data analysis was performed using descriptive statistical techniques, data instrument testing,, multiple regression analysis, and hypothesis testing using IBM SPSS Statistics 25 software. The results showed that partially, price did not affect consumer purchasing decisions on Avoskin products, while product quality did affect consumer purchasing decisions on Avoskin products. Simultaneously, both price and product quality have a significant influence on consumer purchasing decisions on Avoskin products.